Omega‐3 fatty acids and neurocognitive ability in young people at ultra‐high risk for psychosis. Issue 4 (6th September 2020) - McLaverty, Alison; Allott, Kelly A.; Berger, Maximus; Hester, Rob; McGorry, Patrick D.; Nelson, Barnaby; Markulev, Connie; Yuen, Hok Pan; Schäfer, Miriam R.; Mossaheb, Nilufar; Schlögelhofer, Monika; Smesny, Stefan; et al.
Abstract: Background: Neurocognitive impairments are core early features of psychosis and are observed in those at ultra‐high risk (UHR) for psychosis. The aim of the present study was to explore whether neurocognition is associated with polyunsaturated fatty acids (PUFAs), as has been observed in other clinical populations. Method: Erythrocyte levels of total omega‐3‐and omega‐6 PUFAs the omega‐3/omega‐6 ratio, were measured in 265 UHR individuals. Six domains of neurocognition as well a Composite Score, were assessed using the Brief Assessment of Cognition in Schizophrenia. Pearson's correlations were used to assess the relationship between PUFAs and neurocognition. All analyses were controlled for tobacco smoking. Results: Verbal Fluency correlated positively with eicosapentaenoic acid ( P = .024) and alpha‐linolenic acid ( P = .01), and negatively with docosahexanoic acid ( P = .007) and Working Memory positively correlated with omega‐3/omega‐6 ratio ( P = .007). Conclusions: The current results provide support for a relationship between Verbal Fluency and omega‐3 PUFAs in UHR. Further investigation is required to elucidate whether these biomarkers are useful as risk markers or in understanding the biological underpinning of neurocognitive impairment in this population.